Sex differences in injury rates in team-sport athletes: A systematic review and meta-regression analysis - Zech, A.; Hollander, K.; Junge, A.; Steib, S.; Groll, A.; Heiner, J.; Nowak, F.; Pfeiffer, D.; Rahlf, A. L. (Journal of Sport and Health Science, 2022)
Background Team-sport players have a particularly high injury risk. Although female sex is considered a risk factor, it is still unknown whether female and male team-sport players, in fact, differ in their injury rates. We aimed to compare injury rates between female and male players by systematically reviewing and meta-analyzing injury surveillance studies of both sexes in order to evaluate sex-specific differences in team-sport injuries.